Risk Factors for Short Stature in Children Born Small for Gestational Age at Full-Term - Ling, Lan; Chen, Ting; Zhang, Xin-Hua; Pan, Min-Hong; Gong, Hai-Hong; Zhang, Li-Na; Zhao, Meng; Chen, Xiao-Qing; Cui, Shu-Dong; Lu, Chao (Frontiers in Pediatrics, 2022)
Objective: The aim of this study was to identify the risk factors associated with short stature in children born small for gestational age (SGA) at full-term. Methods: This was a retrospective study. The subjects were full-term SGA infants who were followed up until the age of 2 years. The risk factors for short stature were identified with univariate and multivariate analysis. Results: Of 456 full-term SGA children enrolled in this study, 28 cases had short stature at 2 years of age. A significant decrease of placental perfusion was found in the short children group with intravoxel incoherent motion (IVIM) technology, which was an advanced bi-exponential DWI model of Magnetic Resonance Imaging (MRI) (p = 0.012). Compared to non-short children born small for gestational age at full-term, the short children group underwent an incomplete catch-up growth. Mothers who suffered from systemic lupus erythematosus were more likely to have a short child born small for gestational age (p = 0.023). The morbidity of giant placental chorioangioma was higher in the short children group. The pulsatility index, resistivity index and systolic-diastolic ratio of umbilical artery were higher in the short children group than those in the non-short control (p = 0.042, 0.041 and 0.043). Multivariate analysis demonstrated that decrease of perfusion fraction (fp) in IVIM of placental MRI, chromosomal abnormalities, short parental height, absence of catch-up growth, were associated with a higher risk of short stature in children born small for gestational age at full-term. Conclusion: Risk factors for short stature in full-term SGA children at 2 years of age included decrease of perfusion fraction fp in IVIM of placental MRI, chromosomal abnormalities and short parental height.